Automated diagnostics and analytics for buildings - Capehart, B. L. (Barney L.); Brambley, Michael R. (2015)
Provides information to a broad audience on the state of automated fault detection and diagnostics for buildings applications, the benefits of those applications. Covers topics such as emerging diagnostic technology, examples of field deployments, the relationship to codes and standards, automated diagnostic tools presently available, guidance on how to use automated diagnostics, and related issues.
"With the widespread availability of high-speed, high-capacity microprocessors and microcomputers with high-speed communication ability, and sophisticated energy analytics software, the technology to support deployment of automated diagnostics is now available, and the opportunity to apply automated fault detection and diagnostics to every system and piece of equipment in a facility, as well as for whole buildings, is imminent. The purpose of this book is to share information with a broad audience on the state of automated fault detection and diagnostics for buildings applications, the benefits of those applications, emerging diagnostic technology, examples of field deployments, the relationship to codes and standards, automated diagnostic tools presently available, guidance on how to use automated diagnostics, and related issues"--Page 4 of cover.
0
Includes bibliographical references and index.
Keywords: Intelligent buildings; Buildings -- Mechanical equipment -- Automatic control; Structural analysis (Engineering); Electronic apparatus and appliances